The development and evaluation of video in teaching fasting in selected secondary schools in Kuala Lumpur and Selangor, Malaysia - Azharuddin Sahil (Institute of Education, International Islamic University Malaysia, 2007)
Two main focuses of this study are to produce a video drama as an alternative approach to teaching fasting since some Islamic education teachers who teach at secondary school in Malaysia have no time to explore all aspects of fasting; physical, psychological, sociological and spiritual. Secondly, it is to see how students perceive fasting, their understanding and internalisation of fasting and the video itself after the lesson. A special drama was scripted and filmed. Production was carried out rigorously with the cooperation of certain bodies. The video drama was designed based on the ADDIE'S model by focusing on answering recent problems of teaching 'fasting' among secondary school students based on a needs analysis from a classroom observation conducted prior to writing the video script. The video drama was managed to cover the four aspects of fasting by dramatising others' experience of daily activities. All these aspects were taken into account to enhance the teaching-learning of 'fasting'. The product was evaluated formatively by professionals, teachers. postgraduate students. and secondary school students. To implement and evaluate summatively, eight form two classes out of 27 classes were randomly selected from eight secondary schools in Kuala Lumpur and Selangor, bringing the total number of students to 229. The students were administered to see their perception, understanding and internalisation of fasting as well as the video through open-ended questions administered immediately after the lesson. Most students perceived 'fasting' as a stronger, more beneficial and special ibadah (Islamic practice) compared to others. After watching the video drama, they responded positively towards using video drama in teaching fasting and admitted that their understanding and internalization had improved.